Growth and Production of Brachiaria brizantha cv. MG5 in Three Difference Regrowth Phase Treated by Gamma Radiation Dose - A. N. Respati; N. Umami; C. Hanim (Tropical Animal Science Journal, 2018)
This study was aimed to determine the effect of dose of gamma radiation of seeds on plant growth and plant production of Brachiaria brizantha cv. MG5 during 3 different growth phases. The variables measured were plant growth parameters (height and length of plant, number of leaves and tillers) and production (dry matter and organic matter productions). Data were analyzed in a 5 x 3 factorial design. The first factor was dose of gamma radiation consisted of 5 levels i.e., 0, 100, 200, 300, and 400 Gy. The second factor was regrowth phase consisted of 3 levels i.e., growth phase 1, growth phase 2, and growth phase 3. The difference between means was analyzed using Duncan’s Multiple Range Test (DMRT). The results showed that dose of gamma radiation influenced the plant growth and production (P<0.05) on different growth phases. The dose of 100 Gy gamma radiation showed the highest height and length, as well as dry matter and organic matter productions. The dose of 200 Gy gamma radiation showed the highest number of leaves and tillers. During regrowth phase 2, the grasses showed the highest of height, number of leaves and tillers, and organic matter production, while during regrowth phase 3, the grasses showed the highest length (P<0.05). There was an interaction between the dose of gamma radiation of seeds and regrowth phases on the growth and production  of B. brizantha cv. MG5 (P<0.05). The dose of 100 Gy radiation of seeds and regrowth phase 2 gave the best interaction.  In conclusion, the dose of 100 Gy radiation of seeds gave the best growth and production of B. brizantha cv. MG5 during regrowth phase 2.